Tingkat Adopsi Sistem Tanam Jajar Legowo 2:1 Di Kelompok Tani Mina Sri Jaya Desa Sepanjang Kecamatan Glenmore Kabupaten Banyuwangi Jawa Timur - NINGTYAS, RISTA AYU; ASTITI, NI WAYAN SRI; HANDAYANI, M. TH. (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract The Level of Adoption of Jajar Legowo 2:1 System in the Farmer’s Group ofMina Sri Jaya of Sepanjang Village, the Sub-District of GlenmoreBanyuwangi Regency, East Java One of the sub sector of agriculture is contained in sub-farms. Pigs become one of the most popular animals to be developed in several regions in Indonesia, especially Bali. One pig farm in the province of  Bali, located in Tabanan and is located in the center of Tabanan the pig breeding business in UD Sindi Mandiri located at Bongan village, District of  Tabanan, Bali. The purpose of this research was conducted to determine the feasibility of financial, non-financial, and constraints - constraints faced by businesses pigs. Pigs effort financially viable if the review of the value from  break even point, payback period, net present value, net benefit/cost ratio, gross benefit/cost rati , internal rate of return and sensitivity analysis. The  non  financial  businesses  pigs  feasible if viewed from the technical aspects, marketing aspects, management aspects, legal/law aspects and environmental aspects. While constraints - constraints faced have been overcome by the breeder. Pig breeders need to develop marketing strategies, technology infrastructure in order to be efficient production, increased quality and production can be increased.
Keywords: adoption; farmers; system of Jajar Legowo 2:1